Enhancing sustainable agricultural performance in selected Chinese region: the role of food supply chain management, resource utilization, and government support - Erfanian, Sahar; Zhou, Yewang; Baloch, Qadar Bakhsh (Frontiers in Sustainable Food Systems, 2024)
IntroductionAs global food security and environmental sustainability become increasingly critical, understanding the factors that enhance sustainable agricultural performance is paramount. In this context, This study investigates the relationship between food supply chain management, resource utilization, sustainable agricultural practices, and sustainable agricultural performance within the Chinese market, focusing on the moderating role of government support.MethodsData were collected through 480 structured questionnaires distributed across Changsha, Wuhan, and Guangzhou and analyzed using a two-stage SEM-ANN approach.Results and discussionThe findings reveal that sustainable agricultural practices significantly mediate the relationship between food supply chain management and sustainable agricultural performance. Moreover, sustainable agricultural practices also mediate the relationship between resource utilization and sustainable agricultural performance. Resource utilization was found to sequentially mediate the relationships between food supply chain management, sustainable agricultural practices, and sustainable agricultural performance. Additionally, government support was identified as a crucial moderator in strengthening the relationship between sustainable agricultural practices and performance. The findings have significant implications for policymakers, agricultural managers, and researchers, offering insights into strategies for improving agricultural sustainability in China and potentially other similar contexts.